Reality and other stories - Lanchester, John (W. W. Norton & Company, Inc., 2021)
"Ghost stories for the digital age by the Booker Prize-longlisted author of The Wall. In 2017, inspired in part by Henry James' "The Turn of the Screw," the acclaimed English novelist John Lanchester published a ghost story in The New Yorker. "Signal" was a sensation among readers and was featured on public radio-and it was the first short story of any kind Lanchester had ever written. Since then he's written several more eerie stories of contemporary life and the perils of technology that plunk the reader down in the uncanny world of The Twilight Zone or Black Mirror, and Reality and Other Stories gathers the best of them. A mysterious tall man haunts a country house in search of a cell signal; a translator at an academic conference starts hearing things over his headset that nobody should hear; a family discovers their dependence on the latest technological gadget goes to the very foundations of human relations; and the merry contestants in a reality TV show may actually be... somewhere very hellish indeed. Reality and Other Stories is a book of disquiet that captures the severe disconnection and distraction of our time"--